( 1 − 2 2 1 ) ( 1 − 3 2 1 ) ( 1 − 4 2 1 ) ⋯ ( 1 − n 2 1 ) = 1 6 n + 1
Find positive integer n satisfying the equation above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can change (1 - 2 2 1 ) to ( 2 2 2 2 - 2 2 1 ), which simplifies to 2 2 2 2 − 1 . Simplifying the rest of the equation, we get ( 2 2 2 2 − 1 ) ( 3 2 3 2 − 1 ) ... ( n 2 n 2 − 1 ) = 1 6 n + 1 . Since we know that a 2 - b 2 = ( a - b ) ( a + b ), we can simplify ( 2 2 − 1 ) to (2 - 1) (2 + 1). Doing the same thing to the rest of the equation, we get ( 2 2 ( 2 − 1 ) ( 2 + 1 ) ) ( 3 2 ( 3 − 1 ) ( 3 + 1 ) ) ... ( n 2 ( n − 1 ) ( n + 1 ) ) = 1 6 n + 1 . Simplifying that, we get 2 2 3 3 . . . n 2 ( 2 − 1 ) ( 2 + 1 ) ( 3 − 1 ) ( 3 + 1 ) . . . ( n − 1 ) ( n + 1 ) = 1 6 n + 1 . Focusing on the numerator, ( 2 − 1 ) ( 2 + 1 ) ( 3 − 1 ) ( 3 + 1 ) ( 4 − 1 ) ( 4 + 1 ) ( 5 − 1 ) ( 5 + 1 ) ( 6 − 1 ) ( 6 + 1 ) . . . ( n − 1 ) ( n + 1 ) , we can see that (2 + 1) and (4 - 1) both equal 3, (3 + 1) and (5 - 1) both equal 4, (4 + 1) and (6 - 1) both equal 5, and so on. Rearranging the numerator, we get ( 2 − 1 ) ( 3 − 1 ) ( 2 + 1 ) ( 4 − 1 ) ( 3 + 1 ) ( 5 − 1 ) ( 4 + 1 ) ( 6 − 1 ) ( 5 + 1 ) ( 7 − 1 ) ( 6 + 1 ) ( 8 − 1 ) . . . ( ( n − 3 ) + 1 ) ( ( n − 1 ) − 1 ) ( ( n − 2 ) + 1 ) ( n − 1 ) ( ( n − 1 ) + 1 ) ( n + 1 ) . Simplifying, we get 1 × 2 × 3 2 4 2 5 2 6 2 7 2 . . . ( n − 2 ) 2 ( n − 1 ) 2 × n × ( n + 1 ) . Adding this to the equation, we get 2 2 3 3 . . . n 2 1 × 2 × 3 2 4 2 5 2 6 2 7 2 . . . ( n − 2 ) 2 ( n − 1 ) 2 × n × ( n + 1 ) = 1 6 n + 1 . Now, we can simplify the same factors in the numerator and denominator to get 2 n n + 1 = 1 6 n + 1 . Since the numerators are the same in both sides of the equation, we know 2 n = 16. Dividing by two on both sides, we find the solution of n = 8 .
Using the differences of two squares, the equation can be expressed as (1- 2 1 )(1+ 2 1 )(1- 3 1 )(1+ 3 1 )...(1- n 1 )(1+ n 1 ).
After simplifying, 2 3 × 2 1 × 3 4 × 3 2 × ... × n n + 1 × n n − 1
And if we rearrange it such that the n n − 1 portion comes before the n n + 1 portion of (1- n 2 1 ), 2 1 × 2 3 × 3 2 × 3 4 × ... × n n − 1 × n n + 1
The n n + 1 portion of the kth term when multiplied with the n n − 1 portion of the (k+1)th term equals to one: ( k k + 1 ) × ( k + 1 ) ( k + 1 ) − 1 = 1
Therefore, everything in the middle gets cut out. What's left is the n n − 1 portion of the very first term (1- 2 1 ) and the n n + 1 portion of the nth term. Therefore, leaving you with 2 1 × n n + 1 = 2 n n + 1 => 2 n n + 1 = 1 6 n + 1
Thus, for the equation to be true, n = 8 .
1 6 n + 1 1 6 n + 1 2 n = ( 1 − 2 2 1 ) ( 1 − 3 2 1 ) ( 1 − 4 2 1 ) ⋯ ( 1 − n 2 1 ) = ( 2 2 ( 2 − 1 ) ( 2 + 1 ) ) ( 3 2 ( 3 − 1 ) ( 3 + 1 ) ) ( 4 2 ( 4 − 1 ) ( 4 + 1 ) ) ⋯ ( n 2 ( n − 1 ) ( n + 1 ) ) = ( 2 ) ( 2 ) ( 1 ) ( 3 ) ( 3 ) ( 3 ) ( 2 ) ( 4 ) ( 4 ) ( 4 ) ( 3 ) ( 5 ) ⋯ ( ( n ) ( n ) ( n − 1 ) ( n + 1 ) ) = 2 1 ⋅ n n + 1 ⟹ 2 n n + 1 = 2 n n + 1 = 1 6 ⟹ n = 8
From python
def f(x):
z=1
for a in range(2,x+1):
l=1-(1/(a**2))
z*=l
return z
for q in range(1,100):
if f(q)==(1+q)/16:
print(q)
Output:8
Problem Loading...
Note Loading...
Set Loading...
The product can be rewritten as:
P = k = 2 ∏ n ( 1 − k 2 1 ) = k = 2 ∏ n k 2 ( k − 1 ) ( k + 1 ) = 2 ! ( n ! ) 2 ( n − 1 ) ! ( n + 1 ) ! = 2 n n + 1 = 1 6 n + 1
Therefore n = 8 .